Legal Protection for Teachers from The Threat of Criminal Acts of Assault Against Students in The Teaching And Learning Process At Schools - Laxmi Mahavira Nitisari; Faizin Sulistio; Bambang Sugiri (Faculty of Law, Universitas Pekalongan, 2025)
Legal protection for teachers in facing the threat of criminal acts of violence against students during the learning process at school is becoming an increasingly crucial issue. Teachers have a primary role in guiding and educating students, but in practice they often face a dilemma between enforcing discipline and the risk of criminalization for disciplinary actions. This study aims to analyze the form of legal protection for teachers accused of committing acts of violence against students and to identify the factors causing the accusations and strategies for preventing them. This study uses a normative legal approach with a descriptive method based on literature studies. The main data sources include laws and regulations such as Law Number 14 of 2005 concerning Teachers and Lecturers, the Child Protection Law, and regulations related to the juvenile criminal justice system. The results of the study show that although teachers have the authority to impose sanctions on student disciplinary violations, lack of communication often causes disciplinary actions to be misinterpreted as a form of violence. Factors contributing to the emergence of accusations of violence include psychological differences in students, the character and teaching methods of teachers, imbalances in power relations in the education system, and different cultural norms in society in interpreting discipline. As a protection effort, more specific regulations are needed, strong legal advocacy through teacher professional organizations, and synergy with law enforcement officers. Legal awareness for teachers is also an important factor in avoiding actions that can be categorized as violations of the law. With clear legal protection and support from various parties, it is hoped that teachers can carry out their duties professionally without fear or undue pressure.